Crescimento e produção de caupi (Vigna unguiculata (L.) Walp) irrigado submetido a diferentes fontes de nitrogênio - Saboya, Luciano Marcelo Fallé (1995)
Field studies were carried out aiming to analyse growth and yield responses of cowpea (Vigna unguiculata (L.) Walp) cultivar Epace-10 when subjected to different sources of nitrogen. Plant were grown in a yellow-red Podzolic soil and irrigated by a sprinkler system. Four treatments were defined in function of nitrogen sources. In the Control treatment seeds were not innoculated and grown in residual soil nitrogen (0,02%). In the Innoculated treatment seeds were innoculated with Bradyrhizobium sp and received no additional mineral nitrogen. In the Innoculated + Mineral N treatment seeds were innoculated and one third mineral nitrogen was applied during sowing and two third 20 days after germination (DAG). The amount of nitrogen applied was defined by chemical analysis (20 kg/ha). In the Mineral N seeds were not innoculated and mineral nitrogen was applied as in the previous treatment. In all treatments phosphorus (80 kg/ha) and potassium (20 kg/ha) were applied as indicated by soil chemical analysis. Parameter measurements were made at 30, 50 and 57 DAG. Leaf area showed significant difference between the Control (23,3 dm2) and the Innoculated (42,5 dm2) at the 57 DAG. The shoot dry weight showed significantly difference between the Control (13,5 g) and the Innoculated + Mineral N (36,3 g) at the 50 DAG, while at the 57 DAG the Control (25,3 g) did not different significantly from the Innoculated + Mineral N (30,3 g). The average root dry weight in the Control (1,33 g) was significantly different from the Innoculated (2,20 g) and from Mineral N (2,18 g) at 57 DAG. Shoot/root rations were significantly different between the Control (9,8) and Innnoculated + Mineral N (19,0) at 50 DAG. The Innoculated treatment showed at 50 DAG the highest percentage of efficient nodule (23%), greatest dry weight of nodules (15,5 mg) and greater percentage of nodules in the main root (11,8%) in relation to other treatments. In all treatments the greatest percentage of nodules were in the secondary roots at 30, 50 and 57 DAG. Nitrogen, phosphorus and potassium contents in the shoot did not differ significantly among treatment at 30, 50 and 57 DAG. Parameters related to flowering and pod filling (duration of flowering and reproductive phase, number of flowers/plant, number of pods/plant and percentage of abscission) and of yield (number of pods/plant, number of well-formed pods/plant, number of grain/pod, pod length/plant, weight of 100 grains, total grain weight/plant, pericarp weight/plant, and total grain weight/ha) did not different significantly in alI treatments. However, the highest yield was observed in the Mineral N (2211,25 kg/ha), being 26,6% higher than that of the Control, 19,0% greater than that of Innoculated and 14,8% above that of the Innoculated + Mineral N.